Quantitative analysis on tectonic deformation of active rupture zones - 江在森 牛安福 王敏 黎凯武 方颖 张希 张晓亮 (Acta seismologica sinica, 2005)
Based on the regional GPS data of high spatial resolution, we present a method of quantitative analysis on the tectonic deformation of active rupture zones in order to predict the location of forthcoming major earthquakes. Firstly we divide the main fault area into certain deformation units, then derive the geometric deformation and relative dislocation parameters of each unit and finally estimate quantitatively the slip and strain rates in each segment of the rupture zone. Furthermore, by comparing the consistency of deformation in all segments of the whole rupture zone, we can determine the possible anomalous segments as well as their properties and amplitudes. In analyzing the eastern boundaries of Sichuan-Yunnan block with the GPS velocity data for the period of 1991-2001, we have discovered that the Mianning-Ningnan-Dongchuan segment on the Zemuhe-Xiaojiang fault zone is relatively locked and the left-lateral shear strain rate here is higher.